Elas representam quem, cara pálida? : um estudo sobre a representação política das Deputadas Estaduais do Rio Grande do Sul (2007-2011) - Silveira, Luana Borges da (2014)
The aim of this study is to analyze the political representation of women through Rio Grande do Sul's female state representatives' performance from 2007 to 2011. We chose Rio Grande do Sul to do our research because we have always followed the path of these Parliamentarians with "curiosity" regarding their projects and their political agendas. That is precisely why we decided to focus our analysis on these State's politicians. We want to verify, in this analysis, whether the women issue is on these parliamentarians' agendas or not. By showing the aspect of women inclusion in politics in contemporary representative democracies, this study provides data on the participation of women in the Legislative Assembly of Rio Grande do Sul, bringing as the central discussion if the parliamentarians raised questions concerning gender relations in society. That is to say, we want to verify if the women subject is discussed in parliament